Cetrorelix promotes cell apoptosis via the PI3K–AKT–FOXO1 pathway in epithelial ovarian cancer - Zhang, Ning; Liu, Yu; Zhang, Xiaodan; Xie, Meng; Zhang, Ying; Hua, Keqin (Frontiers in Oncology, 2025)
IntroductionEpithelial ovarian cancer (EOC) has a dismal prognosis, and recent therapeutic advancements have been limited. The aim of our study was to clarify the role and mechanism of cetrorelix in EOC apoptosis and to evaluate the clinical relevance of GnRHR, AKT, and FOXO1 in EOC patients.MethodsApoptosis was assessed using flow cytometry, Hoechst staining, and Western blotting. FOXO1, p-AKT and GnRHR knockdown via siRNA was performed to reverse cetrorelix-induced apoptosis. Mechanistic insights were explored using apoptosis gene PCR arrays, qRT–PCR, and Western blotting. In vivo efficacy was tested in a xenograft mouse model. Immunohistochemistry (IHC) was used to assess GnRHR, AKT,p-AKT and FOXO1 expression in EOC tissues, and survival analysis was performed using Kaplan–Meier and Cox regression analyses.ResultsCetrorelix facilitated EOC apoptosis both in vitro and in a xenograft model. The results of apoptosis PCR arrays linked cetrorelix treatment to the upregulation of the TNF/TNF receptor superfamily (a FOXO1-dependent mechanism). Mechanistically, cetrorelix upregulated FOXO1 expression, and FOXO1 knockdown attenuated cetrorelix-induced apoptosis. Furthermore, cetrorelix-mediated suppression of p-AKT expression and subsequent FOXO1 activation occurred via the PI3K/AKT signaling axis. This mechanism was substantiated by the findings that the PI3K inhibitor LY294002 mimicked cetrorelix’s effects without producing an additive apoptotic response, and that GnRHR knockdown abrogated cetrorelix-induced apoptosis, confirming receptor specificity. Experiments in xenograft models recapitulated the PI3K/AKT/FOXO1 cascade modulation observed in vitro. However, the in vivo activation status of FOXO1 was not quantitatively assessed or localized within the xenograft tissues. Clinically, FOXO1/GnRHR positivity and AKT negativity were correlated with early-stage disease (FIGO I-II, p < 0.05), no metastasis (p < 0.05), and improved survival (log-rank p < 0.05). Multivariate analysis revealed GnRHR positivity, AKT negativity, low-grade pathological type and early FIGO stage as independent risk factors for improved overall survival.ConclusionThese findings suggest that cetrorelix may induce EOC apoptosis via the PI3K/AKT–FOXO1 pathway, which provides mechanistic support for the therapeutic potential of GnRH antagonists in EOC management. Moreover, the identified critical regulatory pathways are prospective therapeutic targets for EOC management.